Spring wheat grain yield and quality depending on site-based fertilizing - Jaan Kuht; Toomas Tõrra; Jaanus Kilgi; Arvo Makke (Agraarteadus, 2013)

(untitled)
In 2011 the experiment with spring wheat 'Manu' was carried out on the experimental field of the Estonian University of Life Sciences. The experiment was carried out in the soils with different content of organic carbon (Corg): background A with higher Corg content > 1.7% and background B with lower Corg content ≤ 1.7%. Four fertilizing treatment were used: 1) unfertilized, control (K); 2) conventional fertilizing (T), where all amounts of mineral fertilizers (N120P52K100) were applied before sowing; the amount of fertilizer was supposed to ensure the grain yield level of 4 t ha-1; 3) application of fertilizers according to the soil information (MI) – all amounts of mineral fertilizers (NPK) were applied before sowing; the amounts of mineral fertilizers were adjusted according to the nutrient content of the soil; 4) application of fertilizers according to the soil and plant information (MILV) – mineral fertilizers applied firstly as in MI treatment and additionally at plant development stage BBCH4 the foliar fertilizer added according to the plant nutrition level (determined by chlorophyll meter). Grain yield levels of different backgrounds (A and B) differed in site based fertilization treatments (MI and MILV) less than in control and conventional treatments (26.7 and 19.4% versus 47.4 and 45.5%, respectively). Despite the fact that the amounts of fertilizers were in MI treatment up to one third smaller than of conventional treatment T, the majority values of grains quality of these treatments were statistically the same.